RISK OF EATING DISORDERS AND BODY DISSATISFACTION AMONG GYM-GOERS IN ANKARA, TURKEY - Yesildemir,Ozge (2022)
ABSTRACT Introduction: Although regular exercise is widely recommended to promote optimal health, it is thought that gym-goers are at risk for body dissatisfaction and eating disorders. Objective: This study assessed the risk of eating disorders and the prevalence of body dissatisfaction in gym-goers enrolled in a gym located in the city of Ankara, the capital of Turkey. Methods: This cross-sectional study was conducted with 206 gym-goers, 102 males (mean age of 25.8±7.86 years) and 104 females (mean age of 26.5±9.07 years), who regularly exercised at least twice a week at this gym during the years 2018 to 2019. Demographic characteristics and exercise status of the participants were collected through face-to-face interviews via a questionnaire form. The REZZY (SCOFF) questionnaire was administered to determine the risk of eating disorders and the Stunkard Figure Rating Scale was administered to determine body dissatisfaction. Results: The mean REZZY score in females (1.4±1.21) was higher than in males (0.8 ± 1.05) (p<0.01). In males, 26 out of 102 (25.5%) had a score indicating a risk of eating disorders. In females, 44 out of 104 (42.3%) had a score indicating a risk of eating disorders. The risk of eating disorders is higher in females than in males (p<0.05). While 49.0% of males stated that their current body size is greater than the ideal body size, 76.0% of females said that their current body size is greater than the ideal body size. Conclusion: Consequently, it was determined that gym-goers were a risk group in terms of eating disorders and body dissatisfaction. Level of Evidence: III; Cross-sectional study.